2016
DOI: 10.3862/jcoloproctology.69.499
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence after Intersphincteric Resection

Abstract: Complications after intersphincteric resection related to defecation disorder include increase in stool frequency, urgency of defecation, and fecal incontinence. When the use of an absorbent pad is continued, the defecation function improves over time and then levels out after approximately two years. Anal manometry is used to monitor the defecation function, but there is often a poor correlation between the findings from manometry and the actual defecation situation. Proctectomy preserving the anus has decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…On the other hand, Inoue et al reported on patients with corneal endotheliitis in which genomic DNA for HHV-7 was detected by PCR analysis in the aqueous humor samples [ 3 ]. In addition, Shimomura used multiplex real-time PCR and detected the DNA of HHV-7 in the tear fluid before and after phacoemulsification and aspiration cataract surgery and after penetrating keratoplasty [ 2 ]. There have not been any reports of HHV-7 being detected in the vitreous fluid except for our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Inoue et al reported on patients with corneal endotheliitis in which genomic DNA for HHV-7 was detected by PCR analysis in the aqueous humor samples [ 3 ]. In addition, Shimomura used multiplex real-time PCR and detected the DNA of HHV-7 in the tear fluid before and after phacoemulsification and aspiration cataract surgery and after penetrating keratoplasty [ 2 ]. There have not been any reports of HHV-7 being detected in the vitreous fluid except for our case.…”
Section: Discussionmentioning
confidence: 99%
“…Human herpesvirus 7 (HHV-7) infections have been associated with roseola infantum, acute hemiplegia of childhood, respiratory tract infections, and hepatitis. It has been reported that the DNA of T. gondii can be detected in the vitreous humor [ 1 ], and the DNA of HHV-7 can be detected in the tear fluid of patients before and after cataract surgery or after penetrating keratoplasty [ 2 ] and in the aqueous humor of patient with corneal endotheliitis [ 3 ]. However, to the best of our knowledge, the DNA of HHV-7 has not been detected in the vitreous.…”
Section: Introductionmentioning
confidence: 99%